Development of Narcotics Prevention in Indramayu District - Hamja, Hamja; Sumartini, Raden Siti; Ismunandar, Denni; Fathimah, Najwa Putri (Gema Wiralodra, 2024)
In Indramayu, the spread of narcotics is not a crisis, but if left unchecked, it will become a crisis for the future of youth in Indramayu. This study aims to determine the development of narcotics trafficking prevention in Indramayu district. The method used is a direct interview with the source. The participants in this study are the Head of the Indramayu Police Drug Unit, the Chairman of the Lemah Mekar District Drug-Free Village, and the Indramayu Regency Pamong Praja Police Unit. The results obtained are that at this time the spread of narcotics is still conducive or always monitored by both the community, babinkamtibmas, and babinsa. The distribution of narcotics in the form of Prohibited Hard Drugs (OKT) still exists but is hidden. Counseling is more effective if it is carried out through a personal approach to adolescents aged 15 to 19 years.